2021
DOI: 10.2174/1570193x17999201026230245
|View full text |Cite
|
Sign up to set email alerts
|

Plants as a Promising Reservoir of Tyrosinase Inhibitors

Abstract: Abstract:: The process of melanogenesis, that takes place in the melanocytes of the epidermis, leads to hyperpigmentation. The biosynthetic pathway for production of melanin involves the enzyme tyrosinase that has been an attractive target for cosmaceutical research. Numerous synthetic, semisynthetic and natural, especially plant-based, inhibitors of tyrosinase have been reported in the literature. In plants, the secondary metabolites like flavonoids, chalcones, stilbenes, tannins, hydroquinone and kojic acid,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…It was indicated that EOs and their main constituents had a wild range of bioactivities, such as antibacterial, antifungal, and anti-inflammatory activities ( 5 , 13 ). Herein, we investigated inhibitory effect of 65 EOs on tyrosinase in vitro .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was indicated that EOs and their main constituents had a wild range of bioactivities, such as antibacterial, antifungal, and anti-inflammatory activities ( 5 , 13 ). Herein, we investigated inhibitory effect of 65 EOs on tyrosinase in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…However, the upregulation of tyrosinase activity and excessive accumulation of melanin would cause skin disorders and related diseases, such as freckles, malignant melanoma, and Parkinson’s disease ( 2 4 ). In nature, fruits and vegetables browning, related with the increase of tyrosinase activity, was confirmed to shorten the shelf life of fruits and vegetables, which causes an unattractive appearance and unpredicted loss in nutritional quality ( 5 7 ). Recent research indicated that kojic acid, widely used for skin whitening and hyperpigmentation preventing, would lead to skin irritation and mutagenic effect on human skin ( 8 10 ).…”
Section: Popular Scientific Summarymentioning
confidence: 99%
“…Until now, many compounds have been addressed for their potent tyrosinase inhibitions, such as flavones, [25] peptides, [26] Schiff bases, [27] and sulfonamide chalcones [28] . Also, some plant extracts were evaluated for their tyrosinase inhibition properties [29–31] …”
Section: Introductionmentioning
confidence: 99%
“…[28] Also, some plant extracts were evaluated for their tyrosinase inhibition properties. [29][30][31] Pancreatic lipase (PL) has been accepted as an important agent of the therapeutic target for curing obesity and is a vital enzyme for the hydrolysis of dietary lipids. [32] PL inhibitors have been used in the treatment of obesity due to reducing the absorption of lipids.…”
Section: Introductionmentioning
confidence: 99%
“…There is great interest in the control of tyrosinase activity, especially through the use of inhibitors, which can be natural or synthetic [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. This enzyme has two activities: firstly, monophenolase activity, catalysing the passage from L-tyrosine to L-dopa, and secondly, diphenolase activity, which catalyses the passage from L-dopa to L- o -dopaquinone [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%